1996
DOI: 10.1111/j.1600-0536.1996.tb02219.x
|View full text |Cite
|
Sign up to set email alerts
|

Patch testing in children

Abstract: 92 children (45 girls, 47 boys), mean age 9.3 years (3-14.75), were referred to the Contact Dermatitis Investigation Unit, Belvidere Hospital, Glasgow, for patch testing during the period 1979-93 for the investigation of allergic contact dermatitis (ACD). The diagnoses at the time of referral were atopic dermatitis (45), non-atopic with localized dermatitis (26), juvenile plantar dermatosis (15), orofacial granulomatosis (2), vaccination reaction (2) and atypical psoriasis (2). In total, there were 55 positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
1
6

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 18 publications
4
36
1
6
Order By: Relevance
“…While some authors (Weston et al, 1986;Barros et al, 1991;Stables et al, 1996) detected similar prevalence in both boys and girls, other (Dotterund & Falk, 1995;Wantke et al, 1996;Goossens & Morren, 2006) reported a higher prevalence in girls. This is especially the case for nickel (Brasch & Geier, 1997;Wöhrl et al, 2003) and after the age of 12 (Rademaker & Forsyth, 1989;Rudzki & Rebandel, 1996;Katsarou et al, 1996;Goossens & Morren, 2006).…”
Section: Prevalence Related To Sexmentioning
confidence: 91%
See 4 more Smart Citations
“…While some authors (Weston et al, 1986;Barros et al, 1991;Stables et al, 1996) detected similar prevalence in both boys and girls, other (Dotterund & Falk, 1995;Wantke et al, 1996;Goossens & Morren, 2006) reported a higher prevalence in girls. This is especially the case for nickel (Brasch & Geier, 1997;Wöhrl et al, 2003) and after the age of 12 (Rademaker & Forsyth, 1989;Rudzki & Rebandel, 1996;Katsarou et al, 1996;Goossens & Morren, 2006).…”
Section: Prevalence Related To Sexmentioning
confidence: 91%
“…Of these, about 56-93% was of current relevance (Weston & Weston, 1984;Pevny et al, 1984b;Fisher, 1994a;Rudzki & Rebandel, 1996;Stables et al, 1996;Manzini et al, 1998;Bruckner et al, 2000;Machovcová et al, 2001;Wöhrl et al, 2003;Heine et al, 2004;Lewis et al, 2004;Jøhnke et al, 2004;Vozmediano & Hita, 2005;Wahlberg & Lindberg, 2006;Goossens & Morren, 2006;Jacob et al, 2008). Among the children with a positive patch test 3.2% to 54.4% had multiple contact allergies (Mortz & Andersen, 1999).…”
Section: Prevalence Of Contact Allergy In a Selected Populationmentioning
confidence: 99%
See 3 more Smart Citations